2017
DOI: 10.1027/1192-5604/a000096
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Perception and Distortion Correlates With Rorschach Cognitive and Interpersonal Variables

Abstract: Abstract. Although emotional intelligence is frequently measured with performance tasks, they are often correlated with self-report measures of personality. The present research compared the scores of two performance tests: the Rorschach Inkblot Method for personality (scored using R-PAS), and the Computerized Test of Primary Emotions Perception for emotional perception and understanding, branches of emotional intelligence. Participants were 93 Brazilian people, including undergraduates and psychiatric outpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…It also moderated treatment success over time. In Brazil, Miguel et al (2017) found FQo%, FQu%, and Popular did not lead to a more accurate ability to identify emotional expressions in film vignettes but the EII-3, TP-Comp, WSumCog, SevCog, and FQ-% predicted distorted perceptions in which respondents clearly identified the wrong emotional experiences.…”
Section: Construct Validitymentioning
confidence: 83%
“…It also moderated treatment success over time. In Brazil, Miguel et al (2017) found FQo%, FQu%, and Popular did not lead to a more accurate ability to identify emotional expressions in film vignettes but the EII-3, TP-Comp, WSumCog, SevCog, and FQ-% predicted distorted perceptions in which respondents clearly identified the wrong emotional experiences.…”
Section: Construct Validitymentioning
confidence: 83%
“…The Rorschach can be a useful, therapeutic tool for assessment as it can elicit curiosity and facilitate healthy social, emotional, and perceptual development during treatment. The case of Ms. A illustrates the Rorschach’s range in developing and implementing personalized treatment (Aschieri et al, 2019; Aschieri & Smith, 2012; Aschieri & Vetere, 2020; Bornstein, 2022; Fantini et al., 2022; Finn et al, 2012; Miguel et al, 2017). Ms. A initially approached the Rorschach with skepticism, but during feedback sessions she wanted to discuss the inkblots most.…”
Section: Discussionmentioning
confidence: 99%